A Framework for (Tele-) Monitoring of the Rehabilitation Progress in Stroke Patients - Jagos, H.; David, V.; Haller, M.; Kotzian, S.; Hofmann, M.; Schlossarek, S.; Eichholzer, K.; Winkler, M.; Frohner, M.; Reichel, M.; Mayr, W.; Rafolt, D. (Applied Clinical Informatics, 2015)
Background: Preservation of mobility in conjunction with an independent life style is one of the major goals of rehabilitation after stroke.Objectives: The Rehab@Home framework shall support the continuation of rehabilitation at home.Methods: The framework consists of instrumented insoles, connected wirelessly to a 3G ready tablet PC, a server, and a web-interface for medical experts. The rehabilitation progress is estimated via automated analysis of movement data from standardized assessment tests which are designed according to the needs of stroke patients and executed via the tablet PC application.Results: The Rehab@Home framework’s implementation is finished and ready for the field trial (at five patients’ homes). Initial testing of the automated evaluation of the standardized mobility tests shows reproducible results.Conclusions: Therefore it is assumed that the Rehab@Home framework is applicable as monitoring tool for the gait rehabilitation progress in stroke patients.
Keywords: Chronic disease; stroke; hemiplegia; gait; medical rehabilitation; motivation; exercise therapy; quality of life